AFLORAMIENTOS Y FORAMINÍFEROS EOCENOS EN EL MACIZO DEL DESEADO, PROVINCIA DE SANTA CRUZ - José L. Panza; Carolina Náñez; Norberto Malumián (Publicación Electrónica de la Asociación Paleontológica Argentina, 2015)
Eocene foraminifera were recovered from outcrops at Puesto del Museo (47° 54'S and 67° 52'W), 190 km north of Puerto San Julián, in the Deseado Massif, Santa Cruz Province. Volcanic and pyroclastic rocks of Jurassic age are dominant in the area. At Puesto del Museo, they are overlain by 15-20 m thick, friable, greenish-gray to reddish-brown coquinoid psamites, which yielded relatively scarce, poorly preserved foraminifera. The most frequent species are: Lobatula lobatula (Walker and Jacob), Polymorphina sp. cf. P subrhombica Reuss, Pararotalia sp., Boltovskoyella sp., and Altasterella sp. The assemblage is of low diversity, composed of rotaliids, with epifaunal forms dominant. It is associated with abundant echinoid spines, bryozoa, shell debris, dark green, mature glauconite, and scarce ostracods, fish scales and teeth, and radiolarians. The whole assemblage suggests a shallow, inner shelf environment, a low rate of sedimentation and firm substrate. It is assigned to the Eocene based on its general features, and to the middle-late Eocene based on the occurrence of Altasterella sp. The known surface flooded by the sea during the Eocene is considerably increased, Puesto del Museo is about 200 km north of the northernrnost occurrence of foraminifera of this age in the Austral Basin. Inasmuch as the Puesto del Museo area belonged to the San Jorge Basin during Late Cretaceous-Danian times, the presence of marine Eocene sediments of the Austral Basin domain suggests a change in the regional slope.